Proceedings of the Society for Experimental Biology and Medicine - Society for Experimental Biology and Medicine (New York, N.Y.) (Malden, MA [etc.] Blackwell Science [etc.], 1904)
List of members in each volume
Proceedings of various branches of the society are included
Published in 3 vol. a year, -2000
Vols. 4-<20> issued in parts
Also issued online
Mode of access: Internet.
One of two records for this title. See other record for holdings in other libraries.
UCLA Library - CDL shared resource.
Keywords: Society for Experimental Biology and Medicine (New York, N.Y.) -- Periodicals; Medicine -- Periodicals; Biology -- Periodicals; Medicine, Experimental -- Periodicals; Physiology -- Periodicals